Effects of transcutaneous electrical acupoint stimulation on early postoperative pain and recovery: a comprehensive systematic review and meta-analysis of randomized controlled trials - Tan, Shi-Yan; Jiang, Hua; Ma, Qiong; Ye, Xin; Fu, Xi; Ren, Yi-Feng; You, Feng-Ming (Frontiers in Medicine, 2024)
Background: Previous studies have indicated beneficial outcomes of transcutaneous electrical acupoint stimulation (TEAS), but high-quality and comprehensive meta-analyses are lacking. The aim was to quantitatively analyze the efficacy and safety of perioperative TEAS on postoperative pain and recovery.Methods: PubMed, Web of Science, EMBASE, and the Cochrane Library were searched through July 2022. Randomized controlled trials (RCTs) that examined the perioperative application of TEAS in adults compared to sham-TEAS and/or non-TEAS were eligible. Cumulative analgesic consumption within 24 hours and rest pain scores at 2, 6, 12, and 24 hours postoperatively were the two coprimary outcomes.Results: Seventy-six RCTs (n= 9665 patients) were included. Patients treated with TEAS experienced a reduction of clinical importance in cumulative analgesic (morphine equivalent) consumption (WMD: -14.60 mg, 97.5% CI: -23.60 to -5.60; p < 0.001) and a reduction of statistical importance in rest pain scores at multiple timepoints within the first 24 postoperative hours. The secondary outcome analysis also identified clinically significant recovery benefits to TEAS during the first 24 hours after surgery. Furthermore, TEAS could effectively reduce opioid-related side effects and did not increase serious side effects.This article describes current evidence about TEAS intervention on early postoperative pain and recovery. The results support the effectiveness of TEAS, but more high-quality evidence of clinical applicability is also needed.